Dynamic Analysis and Fabrication of Single Screw Conveyor Machine - Sundarraj Moorthi; Meikandan Megaraj; Lenin Nagarajan; Alagar Karthick; Murugesan Bharani; Pravin P. Patil (Advances in Materials Science and Engineering)
The design and development of machine tools play a vital role in the current economic growth. It facilitates the reduction of manufacturing cost coping with a quickly changing business environment. During the design of the machine tool, the dynamic characteristics need to be calibrated for avoiding uncertainties. This paper investigates the design, dynamic characteristics, and development of a single screw conveyor machine which is used to blend waste plastic material with catalysts. The conveyor machine model is created based on the idea developed from filament extruder machine with Pro-E solid modelling software. Its multibody dynamic analysis was carried out for the selected operational requirements in the ADAMS View. It shows that when the conveyor screw operated above the velocity of 42 m/s, the deformation will occur at a maximum value of 4.23 mm. The rigid body dynamic was carried out in ANSYS to solve the performance forecasting problems at their design stage. The dynamic analysis results were suggested to improve the conveying machine and driving mechanisms design parameters.